Religious Conflicts, Enslavement, and Sexual Violence - Herzig, Tamar (Renaissance and Reformation / Renaissance et Réforme, 2025)
This article examines the different types of sexual violence inflicted on enslaved females who were captured during the War of Candia (1645–69). Women and girls constituted an exceptionally high percentage of the individuals enslaved in the course of this religiously justified war. Many of the captured Muslims were trafficked to Catholic Europe, where they were subjected to various forms of sexual exploitation. Yet this article suggests that the prolonged conflict also gave rise to Italian slavers’ sexual violence against enslaved females who were, in fact, not Muslims. It then illuminates the role that religious affiliation actually played in shaping local reactions to the rapes, as well as the responses of Church and state authorities to supplications asking to liberate the survivors of repeated sexual abuse. Finally, the article argues that taking sexual violence into consideration complicates our understanding of early modern Mediterranean enslavement, its motivations, and its implications.